Muscle Protein Synthesis Response to Exercise Training In Obese, Older Men and Women - Smith, Gordon I. (2012)
INTRODUCTION: Physical activity and eating are two major physiological muscle growth stimuli. Although muscle protein turnover rates are not different in young and middle-aged men and women, we recently found that the basal rate of muscle protein synthesis is greater and the anabolic response to mixed meal intake is blunted in 65–80 y old women compared to men of the same age. Whether older women are also resistant to the anabolic effect of exercise is not known. METHODS: We measured the rate of muscle protein synthesis (both during basal, postabsorptive conditions and during mixed meal intake) before and after 3 months of exercise training in obese, 65–80 y old men and women. RESULTS: At the beginning of the study (before training) the basal, postabsorptive muscle protein fractional synthesis rate (FSR) was significantly greater in women than in men (0.064 ± 0.006 %·h(−1) vs. 0.039 ± 0.006 %·h(−1), respectively; P <0.01) whereas the meal-induced increase in the muscle protein FSR was greater in men than in women (P <0.05). In men, exercise training approximately doubled the basal muscle protein FSR (P = 0.001) but had no effect on the meal-induced increase in muscle protein FSR (P = 0.78). In women, exercise training increased the muscle protein FSR by ~40% (P = 0.03) and also had no effect on the meal-induced increase in muscle protein FSR (P = 0.51). CONCLUSION: These results suggest that there is significant sexual dimorphism not only in the basal, postabsorptive rate of muscle protein synthesis but also the anabolic response to feeding and exercise training in obese, older adults.